Efektifitas Multimedia dalam Capaian Belajar Kognitif Siswa pada Pembacaan Jangka Sorong Ketelitian 1/128, 1/1000 Inci - Putrarisna, Helmy Citra Ramadhani; Khumaedi, Muhammad; Samsudi, Samsudi; Kriswanto, Kriswanto (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Teaching material on vernier calipers with 1/128 inch and 1/1000 inch precision in Vocational High Schools (SMK) faces numerous challenges due to technical complexity and limitations in visualizing conventional media. This research aims to quantitatively analyze the effectiveness of Audio-Visual-based learning media in enhancing student comprehension. The study employed a pretest-posttest control group design experimental method involving 30 students from the Motorcycle Engineering expertise program at SMK Muhammadiyah 2 Semarang. The participants were divided into two groups: an experimental group (using multimedia) and a control group (using conventional methods). The research instruments were validated by media and material experts, with results indicating high feasibility and reliability (CVR > 0.75, percent agreement of 95% for media and 94% for material). The results of the effectiveness test prove that the average post-test score of the experimental group was significantly higher than the control group, evidenced by an independent samples t-test (t = 7.641, p = 0.000 < 0.05). The N-Gain analysis also showed a significant difference, with the experimental group experiencing an increase in the high category (68%), while the control group only reached the Low category (27%). This demonstrates that the use of interactive visual media is effective in improving students' conceptual understanding and measurement skills. From these results, it can be concluded that PowerPoint-based audio-visual multimedia is proven to be significantly effective in improving student learning outcomes, particularly for material that is visual and complex. This finding supports the implementation of multimedia learning theory within the context of vocational education.